POLA KEPENULISAN DAN KOLABORASI PENELITIAN PADA JURNAL TREUBIA - Wulan, Sri (Direktorat Repositori, Multimedia, dan Penerbitan Ilmiah - Badan Riset dan Inovasi Nasional (BRIN Publishing), 2017)
Studies on the pattern of authorship and the level of research collaboration have been done by many scientific journals, but the study on the journal Treubia has never been done.The Journal Treubia is an english language journal of the Indo-Australian animal taxonomy. Established in 1919 by the director of Plantetuin Lands (now botanical garden) named Dr. M. Treub, for the first time this journal discussed only on plant pests. Now, Treubia is an English-language scietific journal focus on biosystematic, ecological, and conservation aspects of terrestrial and aquatic fauna in the Indo-Australian region. This aim of this study is to determine the pattern of the authorship and the level of collaborative research in the journal Treubia during period 2006-2016. The method used in this study is descriptive by using the data from journal article of Treubia, Research Center for Biology-Indonesian Institute of Sciences. Collection and processing data were conducted in March 2017. The results show that during the period 2006-2016, journal Treubia produced 50 articles. The most authors are male with 91 (71.1%) of the 128 authors. Furthermore, by country, Indonesia is the biggest contributor with 86 authors (67.19%) and the lowest is Australia, Singapore, and Vietnam each of them with 1 author (0.78%). The document type most highly cited is the journals which has been cited in 1,307 papers, and then newsletter and map which have been cited in 1 paper. The author's collaboration rate is 0.7 with the author's index per article is 2.56. Both of numeral rate and index are the positive criterion for assessing the higher quality of published papers.